Autochthonous circulation of Saint Louis encephalitis and West Nile viruses in the Province of La Rioja (Argentina) - Batallán, Pedro Gonzalo (2021)
The St. Louis encephalitis (SLEV) and West Nile (WNV) arboviruses, whichcirculate in Argentina, are maintained in enzootic transmission cycles involving Culexmosquitoes (vectors) and birds belonging to orders Passeriformes and Columbiformes(amplifier hosts). The objective of this work was to determine the circulation of bothviruses among wild birds in a semiarid ecosystem in the Province of La Rioja throughserologic survey. During 2013 spring and fall 2014 a total of 326 wild birds belonging to 41species were captured in areas close to the cities of La Rioja and Chilecito, in the Provinceof La Rioja. While exposure to SLEV and WNV was analyzed in birds? serum throughneutralizing antibodies detection, viral circulation was estimated through apparentseroprevalence of neutralizing antibodies. The exposure of the avian community to viruseswas 3.02% for SLEV and 1.89 % for WNV, while 1.19% corresponded to coinfections. Ourstudy confirms for the first time the circulation of SLEV and WNV in wild birds in theProvince of La Rioja. Besides, it is the first to register neutralizing antibodies for flavivirusin the species Leptotila verreauxi (White-tipped Dove) (WNV) and Melanerpes cactorum(White-fronted Woodpecker) (SLEV). These results suggest that in semiarid ecosystemsfrom northwestern Argentina the requirements and conditions for amplification andenzootic maintenance of SLEV and WNV would be present.